Dynamic FDG PET/CT imaging: quantitative assessment, advantages and application in the diagnosis of malignant solid tumors - Wang, Yiling; Yang, Yuanshan; Li, Jinxin; Cheng, Dezhou; Xu, Hai; Huang, Jinbai (Frontiers in Oncology, 2025)
Dynamic imaging has obtained remarkable achievements among a variety of malignant tumors due to the development of multiple simplified scanning protocols and the emergence of whole-body PET/CT scanners, which promote wider application of dynamic PET/CT. In this paper, we mainly review the acquisition protocols of dynamic imaging, related kinetic parameters, advantages and the application of dynamic PET/CT imaging in malignant tumors, including lung cancer, hepatocellular carcinoma, breast cancer, pancreatic carcinoma, prostate neoplasm, and cancer of head and neck. Dynamic PET/CT imaging is increasingly being applied the diagnosis, staging, efficacy monitoring, and prognosis evaluation of malignant tumors. Although standardized uptake value is the most frequently employed semi-quantitative assessment index for static imaging, it is susceptible to several factors, thus cannot be used to evaluate the tracer kinetic information of the lesion. Dynamic PET/CT imaging can be used to achieve continuous assessment of the metabolic activity of a lesion over a certain time frame through quantitative measurement of kinetic parameters, such as the net uptake rate constant. Compared with conventional static imaging, dynamic scanning can be used for the early estimation of minute metabolic changes in tumors. Besides, dynamic scanning can directly and effectively reflect tracer uptake. Nevertheless, the intricacy of parameter analysis and the lengthy scanning time related to dynamic scanning limits its clinical application. Dynamic imaging has obtained remarkable achievements among a variety of malignant tumors due to the development of multiple simplified scanning protocols and the emergence of whole-body PET/CT scanners, which promote wider application of dynamic PET/CT. In this paper, we mainly review the acquisition protocols of dynamic imaging, related kinetic parameters, advantages and the application of dynamic PET/CT imaging in malignant tumors, including lung cancer, hepatocellular carcinoma, breast cancer, pancreatic carcinoma, prostate neoplasm, and cancer of head and neck.